PENGARUH SALES GROWTH, KOMISARIS INDEPENDEN DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Malik, Muhamad Abdul; Antonius, Antonius; Wulan, Defina Andany; Arifin, Deni; Nofryanti, Nofryanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine and analyze the effect of sales growth, independent commissioners and capital intensity on tax avoidance with firm size as a moderating variable. Sales growth, independent commissioners and capital intensity are used as independent variables and tax avoidance as the dependent variable and firm size as a moderating variable. This research was conducted on coal mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method of determining the sample in this study used a purposive sampling method so that from 27 population companies a sample of 10 companies was obtained. The data in this study were analyzed by panel data regression analysis. The results of this study indicate that sales growth and capital intensity partially have a positive effect on tax avoidance while independent commissioners partially have no effect on tax avoidance. Simultaneously the variables of sales growth, independent commissioners and capital intensity affect tax avoidance. Firm size cannot moderate the relationship between sales growth, independent commissioners and capital intensity on tax avoidance